Physical fitness of school age children post-implementation of an educational intervention to prevent childhood obesity in Morelos, Mexico - Giovanna Gatica-Domínguez; Jessica E Moreno-Saracho; Jesús David Cortés; Santiago Andrés Henao-Moran; Juan A Rivera (Instituto Nacional de Salud Pública, 2018)
Objective. To compare the physical fitness of children from eight elementary schools in Morelos, México after the implementation of an intervention to prevent childhood obesity. Materials and methods. 214 children were randomly selected (111 - intervention community and 103 - control community). Physical fitness was evaluated by the 6 minutes walking test and the 50 meters speed test, as well as the number of steps/day. Results. The median of time in the speed test at the intervention site was 11.3 seconds and 13.8 seconds at the control site (p<0.001). The median distance traveled in the walking test was 550 m in the intervention site and 420 m in the control site (p<0.001). The children of the intervention community took a median of 15 161 steps/ day and those of the control community took 13 749 steps/ day (p<0.05). Conclusions. Children from the intervention community have significantly better physical fitness.